2021
DOI: 10.2147/prom.s290412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Related Distress and Associated Factors Among Type 2 Diabetes Patients Attending Hospitals, Southwest Ethiopia, 2020: A Cross-Sectional Study

Abstract: Introduction Diabetes related distress is the most common psychological co-morbid condition among type 2 diabetes patients. However, although the number of people living with diabetes has continued to increase over the last 10 years, information regarding diabetes related distress is limited in Ethiopia. Objective The present study aimed to assess the prevalence of diabetes related distress and associated factors among type 2 diabetes patients attending hospitals in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 51 publications
7
28
2
Order By: Relevance
“…The Center for Epidemiologic Studies-Depression (CES-D) scale (n=3) [ 25 - 27 ], Patient Health Questionnaire-9 (PHQ-9) (n=3) [ 29 - 31 ], and Hospital Anxiety and Depression Scale (HADS) (n=3) [ 28 , 32 , 35 ] were most often used to measure depression. The Beck Depression Inventory (BDI) (n=1) [ 34 ] and the Zung Self Depression Rating Scale (n=1) [ 33 ] were used in the remaining studies. Social support was assessed by various questionnaires including the Oslo Social Support Scale (n=2) [ 30 , 32 ], Perceived Social Support Scale (PSSS) (n=2) [ 27 , 33 ], Social Provision Scale (n=1) [ 25 ], and other validated questionnaires (n=6) [ 26 , 28 , 29 , 31 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Center for Epidemiologic Studies-Depression (CES-D) scale (n=3) [ 25 - 27 ], Patient Health Questionnaire-9 (PHQ-9) (n=3) [ 29 - 31 ], and Hospital Anxiety and Depression Scale (HADS) (n=3) [ 28 , 32 , 35 ] were most often used to measure depression. The Beck Depression Inventory (BDI) (n=1) [ 34 ] and the Zung Self Depression Rating Scale (n=1) [ 33 ] were used in the remaining studies. Social support was assessed by various questionnaires including the Oslo Social Support Scale (n=2) [ 30 , 32 ], Perceived Social Support Scale (PSSS) (n=2) [ 27 , 33 ], Social Provision Scale (n=1) [ 25 ], and other validated questionnaires (n=6) [ 26 , 28 , 29 , 31 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Beck Depression Inventory (BDI) (n=1) [ 34 ] and the Zung Self Depression Rating Scale (n=1) [ 33 ] were used in the remaining studies. Social support was assessed by various questionnaires including the Oslo Social Support Scale (n=2) [ 30 , 32 ], Perceived Social Support Scale (PSSS) (n=2) [ 27 , 33 ], Social Provision Scale (n=1) [ 25 ], and other validated questionnaires (n=6) [ 26 , 28 , 29 , 31 , 34 , 35 ]. T2DM was assessed using the self-report of physician-diagnosed diabetes (n= 2) and administrative data or medical records (n= 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Female gender and depression were the only factors identified in the meta-analysis of Perrin et al as being associated with DRD, but a plethora of other factors emerged from the literature such as age, body mass index (BMI), glycemic control, duration of diabetes, lifestyle habits, treatment regimens, level of education etc. 7,[10][11][12][13][14][15][16] DRD has important health-related consequences such as worse glycemic outcomes, poorer medication adherence and diabetes self-care, and poorer quality of life. 5,17 A recent study reported that in patients with T2DM, depressive symptoms were associated with lower self-management behavior and higher glycated hemoglobin (HbA1c), while DRD was associated with higher HbA1c, suggesting that patients with both depression and DRD might have worse outcomes.…”
mentioning
confidence: 99%